2017
DOI: 10.1016/j.celrep.2017.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of SF1 Neuron Activity Coordinately Regulates Both Feeding Behavior and Associated Emotional States

Abstract: SummaryFeeding requires the integration of homeostatic drives with emotional states relevant to food procurement in potentially hostile environments. The ventromedial hypothalamus (VMH) regulates feeding and anxiety, but how these are controlled in a concerted manner remains unclear. Using pharmacogenetic, optogenetic, and calcium imaging approaches with a battery of behavioral assays, we demonstrate that VMH steroidogenic factor 1 (SF1) neurons constitute a nutritionally sensitive switch, modulating the compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 40 publications
5
91
2
1
Order By: Relevance
“…This obesity was associated with leptin resistance and reduced energy expenditure as a result of decreased brown adipose tissue (BAT) thermogenesis . Optogenetic and chemogenetic activation of SF‐1 neurones increase insulin sensitivity and whole‐body glucose utilisation at the same time as suppressing food intake . These data provide strong support for a role of the VMH in both glucose and energy homeostasis and indicate a specific function in regulating whole body energy expenditure.…”
Section: Vmhmentioning
confidence: 80%
“…This obesity was associated with leptin resistance and reduced energy expenditure as a result of decreased brown adipose tissue (BAT) thermogenesis . Optogenetic and chemogenetic activation of SF‐1 neurones increase insulin sensitivity and whole‐body glucose utilisation at the same time as suppressing food intake . These data provide strong support for a role of the VMH in both glucose and energy homeostasis and indicate a specific function in regulating whole body energy expenditure.…”
Section: Vmhmentioning
confidence: 80%
“…DM‐VMN neurones are directly responsive to the key adipostatic hormone leptin via leptin‐receptors expressed in this region . In addition, the transcription factor steroidogenic‐factor 1 (SF‐1) is highly expressed in the DM‐ and central portion of the VMN of the adult mouse, and deletion of leptin‐receptors from SF‐1 neurones in mice using a conditional transgenic knockout approach results in obesity . Interestingly, studies in rodents have shown that infusion or microinjection of leptin directly in to the VMH enhances insulin sensitivity and increases glucose uptake in peripheral tissues, including skeletal muscle, heart and interscapular brown adipose tissue : these effects may be driven by a leptin‐activated subset of SF‐1 DM‐VMN GE neurones .…”
Section: Discussionmentioning
confidence: 99%
“…28 Inaddition, the transcription factor steroidogenic-factor 1 (SF-1) is highly ex-pressedintheDM-andcentralportionoftheVMNoftheadult mouse, 29 and deletion of leptin-receptors from SF-1 neurones in miceusingaconditionaltransgenicknockoutapproachresultsin obesity. 28,30,31 Interestingly,studiesinrodentshaveshownthatinfusion or microinjection of leptin directly in to the VMH enhances insulin sensitivity and increases glucose uptake in peripheral tissues,includingskeletalmuscle,heartandinterscapularbrownadipose tissue 32,33 : these effects may be driven by a leptin-activated subset of SF-1 DM-VMN GE neurones. 34 Inlinewiththesefindings, chemogenetic activation of SF-1 VMN neurones stimulates interscapular brown adipose tissue, heart and red-type skeletal muscleglucoseuptake.…”
Section: Discussionmentioning
confidence: 99%
“…The VMN contains many neurons with diverse actions, however, including not only neurons that increase blood glucose and contribute to the CRR but also neurons that promote energy expenditure (10). Indeed, interfering with glutamatergic transmission throughout the VMN decreases energy expenditure and interferes with glucose tolerance as well as blunts the CRR (7), and most manipulations that interfere with overall VMN function primarily decrease energy expenditure, promoting obesity and glucose intolerance (7,(11)(12)(13)(14)(15)(16). Indeed, to the extent that roles in glucose homeostasis for specific VMN subpopulations have been investigated, most of these roles were found to involve modulation of energy expenditure and glucose disposal.…”
Section: Introductionmentioning
confidence: 99%